Development of an IGF1R longevity variant mouse line using CRISPR/Cas9 genome editing. Issue 1 (2020) - Dou, Yan; Darvas, Martin; Sharma, Kavita; Mathieu, Julie; Morton, John; Tan, Heidi; Soto-Palma, Carolina; Angelini, Luise A; J, Sara; Niedernhofer, Laura J; Suh, Yousin; Robbins, Paul D; et al.
No abstract available